Environmental Factors Associated with Spatial and Temporal Distribution of Anopheles (Diptera: Culicidae) Larvae in Sukabumi, West Java, Indonesia. Issue 4 (28th October 2014) - Stoops, Craig A.; Gionar, Yoyo R.; Shinta,; Sismadi, Priyanto; Elyazar, Iqbal R. F.; Bangs, Michael J.; Sukowati, Supratman
Abstract : A 12-mo ecological study of the spatial-temporal distribution of immature stages of Anopheles species was conducted in Sukabumi District, West Java, Indonesia. The study characterized 1, 600 sites from a contiguous coastal and hill zone (0–800-m elevation) of which 64% contained Anopheles larvae. Principal component and multiple logistic regression analyses identified ecological parameters associated with presence of nine [ Anopheles aconitus Doenitz, Anopheles annularis Van de Wulp, Anopheles barbirostris Van der Wulp, Anopheles flavirostris (Ludlow), Anopheles insulaeflorum (Swellengrebel and Swellengrebel de Graaf), Anopheles kochi Doenitz, Anopheles maculatus Theobald, Anopheles sundaicus (Rodenwaldt), and Anopheles vagus Doenitz] of 15 Anopheles species collected. Combined data for all nine species showed increased Anopheles presence associated with wet season periods and higher elevation habitats exhibiting reduced tree canopy coverage, higher water temperatures, and shallower water depths. Habitat variables measured included topography (elevation), water conditions (temperature, pH, salinity depth, and velocity), habitat characteristics (substrate and canopy cover), density and type of aquatic vegetation coverage (riparian, floating, and emergent), and distance from nearest human habitation. Significant relationships were found for nine species when using all habitats in the analysis. Habitat characteristics for three species were refined. An. aconitus and An. barbirostris were associated with higher elevation rice, Oryza savita L., paddies with relatively shallow water depths, higher water temperatures, higher acidity and salinity concentrations, and a greater average distance from human habitation. An. vagus presence in rice paddies was associated with lower elevation fields, deeper and cooler water, less acidic and saline conditions, and habitats closer to human dwellings. Overall, the distribution of Anopheles species in Sukabumi was found to be nonrandom and predictable on the basis of habitat characteristics.